2017
DOI: 10.1111/jop.12655
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis lipopolysaccharide induces over production of CC chemokine ligand 2 via toll‐like receptor‐4 in oral lichen planus

Abstract: Increased TLR-4 expression contributes to the upregulated expression of CCL2 in the epithelium of OLP lesions, which suggests that oral bacteria participate in the pathogenesis of OLP via the TLR-4 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Recently, several studies have suggested that microorganisms may trigger or be responsible for sustaining or exacerbating the chronic course of OLP [ 32 34 ]. Epithelial barrier dysfunction may precede intracellular infection of basal epithelial cells with bacteria, virus, or possibly fungus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have suggested that microorganisms may trigger or be responsible for sustaining or exacerbating the chronic course of OLP [ 32 34 ]. Epithelial barrier dysfunction may precede intracellular infection of basal epithelial cells with bacteria, virus, or possibly fungus.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, the pathogenesis of OLP is associated with dysregulated T-cell responses to exogenous triggers and an antigen-specific mechanism by keratinocytes and Langerhans cells resulting in the activation of T-cells [ 110 ]. It has been observed that the normal buccal fibroblasts secreted weaker cytokines than the OLP associated fibroblast under LPS stimulation [ 110 , 111 , 112 ].…”
Section: Systemic Effects Related To Endotoxins Secreted By Microorganisms Involved In Periodontitismentioning
confidence: 99%
“…Moreover, LPS is the main component of bacterial cell walls and is an endotoxin that can elicit a strong immune response. Although there is no direct evidence to establish the causality of OLP and microbial factors, oral bacteria had been proved to participate in the pathogenesis of OLP via the TLR‐4 pathway (Zeng et al, ). In our study, we have confirmed the levels of TNF‐α and IL‐6 were higher in OLP tissues compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%